2017
DOI: 10.1371/journal.pmed.1002261
|View full text |Cite
|
Sign up to set email alerts
|

Age-related cognitive decline and associations with sex, education and apolipoprotein E genotype across ethnocultural groups and geographic regions: a collaborative cohort study

Abstract: BackgroundThe prevalence of dementia varies around the world, potentially contributed to by international differences in rates of age-related cognitive decline. Our primary goal was to investigate how rates of age-related decline in cognitive test performance varied among international cohort studies of cognitive aging. We also determined the extent to which sex, educational attainment, and apolipoprotein E ε4 allele (APOE*4) carrier status were associated with decline.Methods and findingsWe harmonized longitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

18
105
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 140 publications
(127 citation statements)
references
References 60 publications
18
105
2
2
Order By: Relevance
“…To assess the presence of a group and time effect, where this may change over time, we first determined the existence of time, group and group×time interactions. Age, sex, educational level,26 history of stroke27 and regular physical activity28 were included as covariates of cognitive decline in the multivariable models. All statistical tests were two-sided with an alpha level set at 0.05.…”
Section: Methodsmentioning
confidence: 99%
“…To assess the presence of a group and time effect, where this may change over time, we first determined the existence of time, group and group×time interactions. Age, sex, educational level,26 history of stroke27 and regular physical activity28 were included as covariates of cognitive decline in the multivariable models. All statistical tests were two-sided with an alpha level set at 0.05.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, our study found that higher levels of global cognition at baseline could predict a decline in global cognitive function. This result seems to be inconsistent with the aforementioned finding that higher education levels may hamper cognitive decline in the oldest‐old because the experience of receiving higher education per se could exert as a cognitive reserve, which may in turn eventually result in slowing the cognitive decline . However, it is likely that cognitive function may collapse very rapidly in older people with higher education once the cognitive reserve is broken down .…”
Section: Discussionmentioning
confidence: 64%
“…Accumulating evidence has suggested that education would play an important role as cognitive reserve to prevent age‐related cognitive decline and onset of dementia . A recent meta‐analysis to examine the relationship between age‐related cognitive decline and educational attainment across ethnocultural groups and geographic regions demonstrated that every additional year of education is associated with a rate of cognitive decline . This result was not changed when subjects with dementia were excluded.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inflammatory risk appeared particularly important in populations that did not carry the apolipoprotein ε4 allele, which is known to confer increased risk of AD. By contrast, Lipnicki and colleagues report on harmonized longitudinal data for 14 cohorts from 12 countries [10]: different rates of cognitive decline were seen for those of different ethnicity, for men versus women, and for apolipoprotein ε4 carriers. In work from Blacker and colleagues, the slow conversion rate of patients with mild cognitive impairment in aging cohorts (except for ε4 carriers) is described, with the study suggesting a need for treatment trials that are enriched for participants carrying ε4 [11].…”
mentioning
confidence: 99%